Skeletal age estimation in a contemporary Western Australian population using the Tanner–Whitehouse method. (June 2016) - Maggio, Ariane; Flavel, Ambika; Hart, Rob; Franklin, Daniel
Highlights: It is a contemporary radiographic hand-wrist age estimation study. TW3 RUS method is most accurate for Western Australian females. TW2 Carpal method is most accurate for Western Australian males. Abstract: Various age estimation techniques have been utilised in Australia to evaluate the age of individuals who do not have documentation to determine legal majority/culpability. These age estimation techniques rely on the assessment of skeletal development as visualised in radiographs, CT scans, MRI or ultrasound modalities, and subsequent comparison to reference standards. These standards are not always population specific and are thus known to be less accurate when applied outside of the original reference sample, leading to potential ethical implications. Therefore, the present study aims to: (i) explore the variation in developmental trajectories between the established Tanner–Whitehouse (TW) age estimation standards and a Western Australian population; and (ii) develop specific hand-wrist age estimation standards for the latter population. The present study examines digital anterior–posterior hand-wrist radiographs of 360 individuals 0 to 24.9 years of age, equally represented by sex. Each radiograph was assessed using the RUS, Carpal and 20-bone methods of Tanner et al. The standard error of the estimate (SEE) was calculated for each method (range: ♀ SEE ±0.4–11.5 years; ♂ SEE ±0.9–10.1 years). The most accurate method was TW3 RUS for females and the TW2 Carpal system for males. The 50th centile skeletal maturity scores for each year age group were plotted against average chronological age to produce polynomial regression standards with a demonstrated accuracy of (♀ SEE ±0.09–3.46 years; ♂ SEE ±0.02–3.42 years) for females and males, respectively. The standards presented here can be used in future forensic investigations that require age estimation of hand-wrist bones in a Western Australian population, however, they are not appropriate for establishing age of majority (18 years), as skeletal maturity was attained on average earlier than 15 years of age in both sexes for all three systems examined.